(untitled) (Modern Problems of Metallurgy, 2019)
The magnitude of the coefficient of thermal linear expansion mainly depends on the temperature and phase composition of the material, the formation of which is determined not only by the chemical composition of the casting, but also by the conditions of its solidification. The objective of the research is to determine the influence of the solidification conditions of metals and alloys on the magnitude of their CTLR in the field of the elastic state of cast copper and its alloys. Research task of this work was to determine the influence of metals and alloys solidification conditions on the value of their CTLE in elastic state region of cast copper and its alloys. Results of these study investigations indicate that during cooling in casting mold temperature transition of technical purity copper from plastic to elastic state is 2860С. Accordingly, these values in bronzes: BrA5 426°С, BrA9Zh3L 359°С, BrO5Z5S5 312°С. Variation in the values of thermal linear expansion coefficients of copper and its alloys which solidified under conditions of free and absolutely hindered linear shrinkage is due to differences in morphology and spatial orientation of crystals formed in alloys, as well as the fractional phases’ composition and defectiveness of the crystal structure.